EFFECT OF WATER CEMENT RATIO AND GGBFS SUBSTITUTION ON COMPRESSIVE STRENGTH AND WORKABILITY OF SCC - Ibnu Faza Febrian; Qomariah Qomariah (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
Self-Compacting Concrete (SCC) is an innovation in concrete technology that is able to flow and solidify independently without the help of mechanical vibration. This study aims to analyze the effect of variations in water to cement ratio (w/c) and cement substitution with Ground Granulated Blast Furnace Slag (GGBFS) optimal value from mortar cube testing, with the optimal value at 30% substitution with a compressive strength of 28.40 MPa. The optimal GGBFS value will be used for the design of SCC specimens and will be tested for workability and compressive strength with variations of 0.35, 0.375, and 0.40. Mix design is made with reference to the recommended composition of the EFNARC standard (2005). The workability test includes slump flow, V-funnel, and L-box, while the compressive strength test will conduct at 7, 14, and 28 days using 15×30 cm cylindrical specimens. The test results showed that increasing the w/c from 0.35 to 0.40 improved the workability of the mix, slump flow increased from 540 mm to 660 mm, the V-funnel time decreased from 15 s to 7 s, and the L-box ratio increased from 0.84 to 0.97. In the compressive strength test, the concrete with w/c 0.40 showed a higher strength increase at 28 days (38.01 MPa) than the other mixes, although the initial value (7 days) was lower. Cost evaluation showed that the use of GGBFS provided an efficiency of Rp37,500 per m³ (±2.94% savings) compared to conventional SCC. Based on the test results and performance analysis, the mix variation with w/b 0.40 and 30% GGBFS substitution was declared as the most optimum composition in terms of workability, strength, and cost efficiency.